Review of budget oversight by parliament Ireland - Downes, Ronnie (OECD Publishing, 2016)
Budget oversight by the Irish parliamentary chambers, the Houses of the Oireachtas, is under-developed by international standards. Many stakeholders and participants question whether the existing process is meaningful or impactful. Nevertheless, there is a strong momentum for reform with Ireland's public administration. Against this background, the OECD presents in this report an analysis of the strengths and weaknesses of Ireland's system of parliamentary engagement in budgeting, and outlines a number of proposals for continued reform by reference to international experience, for consideration by the Houses of the Oireachtas and by other institutional actors and by the political system more generally. JEL Classification: H5, H57, H60 Keywords: Budget process, Dáil, Ireland, Oireachtas, parliament, public administration